FRI0454 Hand function in systemic sclerosis: Effect of occupational therapy on the health status and quality of life. (23rd January 2014) - Stefanantoni, K.; Iliana, S.; Iannace, N.; D'Aluisio, D.; Maset, L.; Passi, L.; Vasile, M.; Scarno, A.; Spadaro, A.; Riccieri, V.
Abstract : Background: Hand involvement highly influences the activities of daily life in most patients with Systemic Sclerosis (SSc). Occupational therapy (OT) studies have rarely investigated for improving of hand function. Objectives: To evaluate the effectiveness after one and three month of OT, based on a self-administered stretching program directed to maximize the hand performance during the activities of daily life using interview-based and self-administered questionnaires to assess hand function. Methods: We enrolled 13 consecutive ScS patients, all female (mean age =62.8 yrs; mean disease duration =14.2 yrs) presenting a clinically evident hand involvement, characterized by pain and reduced range of motion. All patientshad a detailed clinical and laboratory assessment and their organ involvement was also investigated. All patients were evaluated by Canadian Occupational Performance Measure (COPM), with Duruoz Hand Index (DHI), HAQ and mental and physical SF36, at baseline, one and three months after having received instructions to finalize their activities on a self-administred stretching program. Results: Eight (61, 5%) patients had a diffuse form of SSc, while 5 (38, 5%) had a limited form. All of them (100%) were ANA positive: 5 (38.5%) had anti-centromere and 5 (38.5%) had anti-topoisomerase I antibodies. Six (46%) patients had a modified Rodnan skin score over 14; digital ulcers were found in 5 (38.5%) cases. At the end of the one-month stretching program, there was a global improvement in the mean values of COPM performance (5, 4 vs 6, 32) (p=0, 003) and satisfaction (6 vs 6, 49) (p=0, 04) and of total DHI (36 vs 29, 3) (p=0, 09). Mean values of HAQ assessment (1.71 vs 1.38) (p<0.01) and of mental (33.68 vs 41.03) (p<0.008) and physical (28.92 vs.31.75) SF36 scores also improved. The clinical benefit was confirmed after three month for COPM performance (5, 4 vs 6, 3) as well as for COPM satisfaction (6 vs 6, 6) (p=0, 06), for total DHI (36 vs 30) (p=0, 08), for HAQ assessment (2, 0 vs 1, 3) (p=0, 007), and for mental (33, 68 vs 43, 3) and physical (28, 92 vs 29, 3) (p=0, 007) SF36 scores. Conclusions: Our preliminary results show how successful OT together with stretching exercises of the hands can be on the health status and the emotional and physical personal perception of finger joint motion, thus improving quality of life and overall hand function in SSc patients. References: Mugii N et al. J Rheumatol 2006; Mancuso T et al. J Hand Ther 2009;Poole JL Curr Op Rheumatol 2010. Disclosure of Interest: None Declared